Factors Related to the Quality of Life of Students in Pondok Pesantren Al-Wasatiyah Cipondoh, Tangerang Kota - Dwi Setiowati; Dita Fitriyani; Ernawati Ernawati; Ita Yuanita (Jurnal Ilmiah Kesehatan (JIKA), 2026)
The quality of life of adolescents is a crucial aspect considering that this phase is characterized by physical, psychological, emotional, and social changes. Students in Islamic boarding schools face additional challenges such as dense activities, limited family interactions, and academic and religious pressures that have the potential to reduce the quality of life. The purpose of the study was to find out the factors related to the quality of life of students at the Al-Wasatiyah Islamic Boarding School Cipondoh. This study used a correlation design with Spearman Rank test as well as  quantitative approach with a sample of 117 students (total sampling). WHOQOL-BREF, PSS-10, PSQI, Brief COPE, and MSPSS as research instruments. The average student is 15 years old, male (55.6%), and at the junior high school level (64.1%). The majority of subjects had moderate levels of stress (53%), poor sleep quality (97.4%), high social support (51.3%), adaptive coping strategies (60.6%), and moderate quality of life (59.8%). A significant relationship was found between quality of life and gender, sleep quality, coping strategies, and social support with a p-value of < 0.05.  Meanwhile, there was no relationship between age, education level, or stress level with quality of life with a p-value of > 0.05. Further research is recommended to be carried out on Islamic boarding schools with different characteristics, including the pesantren environment, the burden of daily activities, and peer dynamics, as well as developing an applicative approach to improve the quality of life of students.